Didactic sequence: problem solving fraction part-everything and operator in personal learning environment grade 6º - Niño Betancourt, Roberto Alejandro; Chacón Benavídez, José Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The research aimed to strengthen the problem solving of the part-all fraction in continuous, discrete and operator fraction contexts through a didactic sequence implemented in a Personal Learning Environment (PLE), in grade 602 students of the IERD El Dorado Nescuatá Headquarters of the municipality of Sesquilé-Cundinamarca. It was based on a mixed type methodology with an action research design, the sampling was made up of 16 students from the control group -GC- and 15 students from the experimental group -GE-; Three instruments were designed and validated: diagnostic test, didactic sequence and exit test. The results in the diagnostic phase showed an opportunity for improvement regarding the resolution of problems of the fraction as an operator. The didactic sequence was structured in four sessions on the fraction as part of a whole and as an operator. Its implementation was carried out for the experimental group in a PLE guided by various multimedia resources. Overall, better performances were observed in the experimental group in five of the six categories analyzed. When evaluating the impact of the pedagogical intervention, the experimental group achieved better results in solving problems of the fraction as part of a whole and as an operator by combining the use of concrete material and the digital educational resources of the PLE. In the implementation of the didactic sequence, the sampling students appropriated three of the five phases for the resolution of mathematical problems.